2023
DOI: 10.1111/gcb.16661
|View full text |Cite
|
Sign up to set email alerts
|

Identifying historical and future global change drivers that place species recovery at risk

Abstract: Ecosystem management in the face of global change requires understanding how co-occurring threats affect species and communities. Such an understanding allows for effective management strategies to be identified and implemented. An important component of this is differentiating between factors that are within (e.g. invasive predators) or outside (e.g. drought, large wildfires) of a local manager's control. In the global biodiversity hotspot of south-western Australia, small-and medium-sized mammal species are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Furthermore, research has demonstrated that disturbances like fire affect the two species to different extents. Bush rats have been recorded to be severely restricted by fire events and the associated habitat changes [ 26 , 43 ], whereas the effect on common brushtail possums varies between minor negative influence to positive recoveries post-fire [ 26 , 49 ]. Therefore, despite their extensive co-occurrence and overlap in some food and habitat resources, bush rats and common brushtail possums each most likely exploit different parts of these resource axes, and also exhibit different home range sizes and dispersal abilities (Tables 3 and 4 ) [ 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research has demonstrated that disturbances like fire affect the two species to different extents. Bush rats have been recorded to be severely restricted by fire events and the associated habitat changes [ 26 , 43 ], whereas the effect on common brushtail possums varies between minor negative influence to positive recoveries post-fire [ 26 , 49 ]. Therefore, despite their extensive co-occurrence and overlap in some food and habitat resources, bush rats and common brushtail possums each most likely exploit different parts of these resource axes, and also exhibit different home range sizes and dispersal abilities (Tables 3 and 4 ) [ 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%